Comparison of Canadian versus United States Emergency Department Visits for Chronic Obstructive Pulmonary Disease Exacerbation. Issue 6 (2008) - Rowe, Brian H; Cydulka, Rita K; Tsai, Chu-Lin; Clark, Sunday; Sinclair, Douglas; Camargo, Carlos A
Abstract : INTRODUCTION: Despite the frequency of emergency department (ED) visits for chronic obstructive pulmonary disease (COPD) exacerbation, little is known about practice variation in EDs. OBJECTIVES: To examine the differences between Canadian and United States (US) COPD patients, and the ED management they receive. METHODS: A prospective multicentre cohort study was conducted involving 29 EDs in the US and Canada. Using a standard protocol, consecutive ED patients with COPD exacerbations were interviewed, their charts reviewed and a two-week telephone follow-up completed. Comparisons between Canadian and US patients, as well as their treatment and outcomes, were made. Predictors of antibiotic use were determined by multivariate logistic regression. RESULTS: Of 584 patients who had physician-diagnosed COPD, 397 (68%) were enrolled. Of these, 63 patients (16%) were from Canada. Canadians were older (73 years versus 69 years; P=0.002), more often white (97% versus 65%; P<0.001), less educated (P=0.003) and more commonly insured (P<0.001) than the US patients. US patients more commonly used the ED for their usual COPD medications (17% versus 3%; P=0.005). Although Canadian patients had fewer pack-years of smoking (45 pack-years versus 53 pack-years; P=0.001), current COPD medications and comorbidities were similar. At ED presentation, Canadian patients were more often hypoxic and symptomatic. ED treatment with inhaled beta-agonists (approximately 90%) and systemic corticosteroids (approximately 65%) were similar; Canadians received more antibiotics (46% versus 25%; P<0.001) and other treatments (29% versus 11%; P=0.002). Admission rates were similar in both countries (approximately 65%), although Canadian patients remained in the ED longer than the US patients (10 h versus 5 h, respectively; P<0.001). CONCLUSIONS: Overall, patients with acute COPD in Canada and the US appear to have similar history, ED treatment and outcomes; however, Canadian patients are older and receive more aggressive treatment in the ED. In both countries, the prolonged length of stay and high admission rate contribute to the ED overcrowding crisis facing EDs.